Rose in chains - Soto, Julie, 1988- (Soto, Julie, 1988- Evermore trilogy, 2025)
"The war is over, the dark forces have won, and the hero who was supposed to have saved them is dead. The prophecy lied. They were supposed to win this war. Instead, Briony Rosewood watches, shattered and grief-stricken, as her brother is killed, her kingdom falls, and her home is overrun by their enemies. Now Evermore is no more... and Briony is sold at an auction -- prized only for her remarkable magic. But defeat isn't nearly as agonizing as being 'sold' to Toven, scion of the powerful and devious Hearst family, because Briony knows Toven all too well from his merciless taunting all through school. Now he's a grown man Briony cannot ignore -- silver-haired and impossibly, unfairly, beautiful. And while Toven is most definitely her enemy, he's something else, too. Something unexpected. But in a world where magic can instantly crush a human heart and even thoughts can be stolen, there can be no such thing as love. Not for Briony. A secret rebellion is brewing, and she needs to find a way to escape her cage and join it. Yet despite the horrors of her new world and the role she must learn to play within it, all is not lost. Help -- and hope -- may yet arise in the most unlikely of places..." --